Health-Related Social Control over Physical Activity: Interactions with Age and Sex - Cotter, Kelly A. (Journal of Aging Research, 2012)
Despite the disease prevention benefits of engaging in life-long regular physical activity, many adults remain sedentary. The social environment provides an important context for health and health behavior across the lifespan, as well as a potential point of intervention for increasing physical activity. Self-reports of perceived social support, social strain, positive social control, and negative social control were examined for their cross-sectional relationships to physical activity frequency in purposive samples of younger and older adults (N=371, ages from 18 to 97, 68% women). Hierarchical regression analyses revealed that perceived support and perceived strain were not correlated with physical activity. However, age and sex interacted with social control, such that more positive social control was associated with more frequent physical activity for younger men. Furthermore, more positive and negative social control were significantly associated with less frequent physical activity for older men, while social control was not associated with physical activity among women. While younger men may be encouraged toward healthier behaviors by positive social control messages, social control attempts may backfire when targeting older men. Implications for physical activity promotion are discussed.